A conservação da diversidade de anuros no cerrado brasileiro - Lima, Luciana Signorelli Faria (2014)
Land use activities have been frequently transforming broad native areas into pastures or plantations. This process turned out to be a global problem and is known as one major responsible for declinesin various taxonomical groups. Frogs are one of the most threated groups among vertebrates, from which species with aquatic larvae are more susceptible. Such populations follow metacommunity dynamics and can be structured in function of combined processes, such as patch dynamics, species ordination dynamics, mass effect and neutral dynamics. Nevertheless, the lack of knowledge with respect to anuran species occupation and richness patterns in local and regional scale poses as a threat to their conservation. The aim of my work is to provide relevant information to the conservation of anurans in the Brazilian Cerrado. I investigated regional and local scale patterns and identified factors related to richness and occupation of anuran species that breed in Cerrado ponds. For that, I have collected data in the state of Goiás, which is the only Brazilian state totally inserted in the Cerrado biome and that follows that same tendency of habitat loss as the whole biome (due to agriculture expansion). In Chapter I present the first official list for the whole state of Goiás, with the objective to cover inventory gaps. In Chapter II, I explore local and landscape factors that determine local and regional diversities of anurans. I also assess the effects of area, heterogeneity, productivity and local and landscape habitat complexity over alpha and beta diversities of anurans. In Chapter III, I approach one of the most classic and controversial models for the conservation of the species, known as "SLOSS" (single large or several small). This model should be considered especially when the goal is to preserve as many frog species associated with ponds.Finally, in Chapter IV, I built occupation models to assess the effects of amount of remaining habitats, isolation between remnants as well as local characteristics on the occurrence of some species of amphibians typical Brazilian Cerrado.